Synthesis and characterizations of highly luminescent 5-isopropoxybenzo[rst]pentaphene - Islam S. Marae; Jingyun Tan; Rengo Yoshioka; Zakaria Ziadi; Eugene Khaskin; Serhii Vasylevskyi; Ryota Kabe; Xiushang Xu; Akimitsu Narita (Beilstein Journal of Organic Chemistry)
A benzo[rst]pentaphene (BPP) substituted by an isopropoxy group (BPP-OiPr) was synthesized in a facile manner. Its photophysical properties were investigated by UV–vis absorption and fluorescence spectroscopy in compassion to pristine BPP and its oxidation product, benzo[rst]pentaphene-5,8-dione (BPP-dione). BPP-OiPr exhibited a significantly enhanced photoluminescence quantum yield (PLQY), reaching 73% in comparison to pristine BPP (13%). BPP-dione, when compared to the parent BPP, also displayed improved absorption and emission from the first excited singlet (S1) state with a PLQY of 62% and an intramolecular charge-transfer character. The rod-like nano- to microcrystals as well as longer wires of these BPPs were also revealed by scanning electron microscopy. The intriguing optical properties of BPP and its derivatives may lead to their application as fluorophores.